Hubungan Efisiensi Bed Occupancy Rate Bor (BOR) Dengan Kepuasan Pasien Rawat Inap RSUD Koesnadi Bondowoso - Hartaty Sarma Sangkot; Elda Ogitalia; Endang Sri Dewi Hatuti Suryandari; Avid Wijaya (Politeknik Negeri Jember, 2024)
The improvement of healthcare service quality has become the primary focus in maintaining the operational success of a hospital. Bed Occupancy Rate (BOR) serves as an indicator of the efficiency in utilizing inpatient facilities, while patient satisfaction reflects a positive response to the provided care. Although BOR has become a common benchmark, it is still unclear whether this efficiency directly impacts patient satisfaction. This study aims to evaluate the correlation between Bed Occupancy Rate (BOR) efficiency and patient satisfaction during inpatient care at RSUD dr. H. Koesnadi Bondowoso. The research method employed is analytical with a cross-sectional approach, involving the entire inpatient population from August to October 2023 (a total of 3,654 patients). A sample of 100 patients was selected using quota sampling based on the Slovin formula. The findings indicate that two pavilions, Dahlia (57.45%) and Mawar (40.94%), are inefficient in terms of BOR. In contrast, three pavilions, Teratai (92.47%), Melati (61.42%), and Bougenville (61.04%), exhibit efficient BOR. Patient satisfaction, measured among 100 respondents, reveals that 84% are very satisfied, while 16% are dissatisfied. Despite differences in BOR efficiency among pavilions, statistical analysis using the Chi-Square test shows no significant relationship (p = 0.054) between BOR efficiency and patient satisfaction at RSUD dr. H. Koesnadi Bondowoso. In conclusion, this study asserts that BOR values do not significantly impact patient satisfaction in the hospital. These findings suggest that other factors may play a role in influencing patient satisfaction during inpatient care at RSUD dr. H. Koesnadi Bondowoso, necessitating further research for a deeper understanding.